Utilization of Solar Water Heaters to Reduce Residential Electrical Load - Majid S. Al-Hafidh; Mudhafar A. Al-Nama; Azher S. Al-Fahadi (UHD Journal of Science and Technology, 2017)
Residential electrical load in Iraq can be divided into five components, lighting, home appliances, heating, cooling and water heating. Water heating component represents the largest residential electric load component in Iraq. The current research aims to test the possibility of using solar water heaters to supply hot water to residential units. Solar water heaters were added to a number of residential units in Mosul city, with the addition of a small electrical heater to provide supplementary heating.